2015
DOI: 10.4028/www.scientific.net/ssp.227.127
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Functional Epoxy Coatings Modified by Carbon Nanoparticles

Abstract: Properties of commercially available epoxy coating were modified using multi-walled carbon nanoparticles (MWCNT) to obtain functional coating with improved abrasion resistance. Simultaneously, corrosion resistance of the epoxy resin could not be negatively affected by the particles addition. Composite coatings with various MWCNT content were prepared and evaluated with regard to their function by abrasion and corrosion tests. We found out that the abrasion resistance of the coatings increased with increasing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The damping ratio of the nanocomposite increased by 300% compared to the baseline composite, highlighting a significant improvement in the vibration damping properties. Diblíková, et al [16] developed epoxy coatings with Multi-Walled Carbon NanoTube (MWCNT) particles, and observed that the abrasion resistance of coatings increased with increasing carbon nanotube content. Grundwürmer et al [17] synthesized organic-inorganic hybrid coatings using sol-gel technology with the addition of ZrO 2 nanoparticles.…”
Section: Nanoscale Reinforcements In Anti-erosion Coatings: State Of the Artmentioning
confidence: 99%
“…The damping ratio of the nanocomposite increased by 300% compared to the baseline composite, highlighting a significant improvement in the vibration damping properties. Diblíková, et al [16] developed epoxy coatings with Multi-Walled Carbon NanoTube (MWCNT) particles, and observed that the abrasion resistance of coatings increased with increasing carbon nanotube content. Grundwürmer et al [17] synthesized organic-inorganic hybrid coatings using sol-gel technology with the addition of ZrO 2 nanoparticles.…”
Section: Nanoscale Reinforcements In Anti-erosion Coatings: State Of the Artmentioning
confidence: 99%
“…While soft and viscoelastic coatings are apparently best to dissipate impact waves, the stiff or stiff particles reinforced coatings should be preferable for abrasion resistance of coatings. For instance, Diblíková et al developed epoxy coating with multiwall carbone nanotube (MWCNT) particles and observed that the abrasion resistance of coatings increased with increasing carbon nanotube (CNT) content.…”
Section: Reinforced and Nanoreinforced Coatingsmentioning
confidence: 99%